Rancang Bangun Aplikasi Administratif Surat Menyurat Pada Dinas Pekerjaan Umum Cipta Karya Dan Tata Ruang Provinsi Jawa Timur - Ginanjar, Moh. Haris; Wurijanto, Tutut; Oktaviani, Oktaviani (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Dinas Pekerjaan Umum Cipta Karya dan Tata Ruang (DPUCKTR) East Java Province is a department that has important role in government budget allocation in General works department. There are 2 business processes, they are incoming and outgoing letters recording. The business process of incoming and outgoing letters is started from the entry of a letter to the administration department, later it is recorded in the controller list to be archieved next. Incoming letters go to the recipient while outgoing letters are sent to the addressed other department or office. The problems that often happen in the company are (1) the management process of the letter takes time and less effective. Considering, there are still numbers of letters that need to be recorded. (2) the saving process of letters archieve storage is susceptible lost, thereby inhibiting letters search.(3) distribution process manually by visiting the stakeholder is susceptible to the late submission of the letters. (4) There is no letters report yet, either monthly or annually. The design of administrative correspondence application is a required application for secretariat in managing the letters .This application is able to facilitate the secretariat in receipt of incoming letters to send outgoing letters as well as the distribution of the letters too. Based on the result of experiment performed, it can be concluded that the system createdÂ to help general works department until the letters are distributed.Keywords: Application, Administrative, Correspondence